Association of Glycosyllated Hemoglobin (Hba1c) Levels to the Severity of Diabetic Foot Ulcer in Type 2 Diabetes Mellitus Patients in RSUP. H. Adam Malik Medan - Muhammad Ishaq Porkas Lubis; Marshal; Muhammad Ali Syahputra (Talenta Publisher, 2022)
Abstrak Introduction: Diabetic ulcers with neuropathy require amputation or time to fully heal. The worse blood sugar control, it will worsen the condition of complications such as diabetic ulcers, diabetic neuropathy, and other complications. Wound healing in diabetic ulcers is influenced by controlled HbA1c levels. Methods: This study is an observational analytic study with a retrospective design used in this study with secondary data. This study is analytical because it aims to obtain the correlation of HbA1c with the severity of diabetic ulcers in patients with diabetes mellitus at H. Adam Malik Hospital. Results: The average age of the patients was 62 with the majority of respondents being male. The dominance of respondents came with Grade IV as many as 17 people, with uncontrolled HbA1c levels as many as 39 people. Using Spearman Corelation test, the value of r = 0.735, 0.736, and 0.785, respecttively for the corelation between HbA1c, Hb and ESR levels with the severity of diabetic foot ulcers ,with a value (p = 0.0001). Conclusion: We found a strong correlation and a significant relationship between HbA1c, Hb, and ESR levels with the severity of diabetic foot ulcers.